Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) Sistem Zonasi Di SMA Negeri 14 Bekasi - Fitri Rachmadhany; Matin Matin (WAHANA, 2021)
This study aims to analyze the implementation policy of PPDB Zoning at SMAN 14 Bekasi to equalize access and high-quality education services. This research was conducted in January 2020. This research focuses on the level of SMA Negeri 14 in Bekasi. Sampling was conducted with a specific objective, namely the favorite high school in the area closest to the capital city of West Java Province. The analysis of this research uses the Van Meter and Van Horn (1975) implementation model approach which includes the size and policy objectives, resources, characteristics of the executing agent, the attitudes (disposition) of the executors, inter-organizational communication and executive activities, economic environment, social, and Politics. Based on the results of the analysis, the results of this study is that the implementation of PPDB Zoning in West Java Province has been successful in efforts to equalize access and quality of education. The distribution of students from the distance side has approached the student's house and in terms of input quality, it has also spread across various schools so that there is no longer a dichotomy between superior and non-superior schools. Key words: Implementation, Policy, school enrollment zoning system Penelitian ini dengan tujuan untuk menganalisis kebijakan implementasi pelaksanaan PPDB Zonasi di SMAN 14 Bekasi dalam upaya pemerataan akses dan layanaan mutu Pendidikan yang tinggi. Penelitian ini dilakukan bulan Januari 2020. Penelitian ini berfokus pada jenjang SMA Negeri 14 di Bekasi. Pengambilan sampel dilakukan dengan tujuan tertentu, yaitu SMA favorit di wilayah terdekat ibukota Provinsi Jawa Barat. Analisis penelitian ini dengan menggunakan pendekatan model implementasi Van Meter and Van Horn (1975) yang meliputi variabel Ukuran dan Tujuan Kebijakan, Sumberdaya, Karateristik Agen Pelaksana, Sikap/ kecenderungan (Disposition) para Pelaksana, Komunikasi Antarorganisasi dan Aktivitas Pelaksana, Lingkungan Ekonomi, Sosial, dan Politik. Berdasarkan hasil analisis, kesimpulan hasil penelitian ini adalah pelaksanaan PPDB Zonasi di Provinsi Jawa Barat sudah berhasil dalam upaya memeratakan akses dan mutu pendidikan. Sebaran siswa dari sisi jarak sudah mendekat ke rumah siswa dan dari sisi mutu input juga telah menyebar di berbagai sekolah sehingga sudah tidak ada lagi dikotomi sekolah unggulan dan non unggulan Kata kunci: manajemen, kebijakan, PPDB System Zonasi